Asymptotics of a fundamental solution system for a quasidifferential equation with measures on the semiaxis - O.V. Makhnei (Karpatsʹkì Matematičnì Publìkacìï, 2014)
With the help of a conception of quasiderivatives asymptotic formulas for a fundamental solution system of a quasidifferential equation with measures on the semiaxis $[0,\infty)$ are constructed. The obtained asymptotic formulas allow to investigate asymptotics of eigenvalues and eigenfunctions of the corresponding boundary value problem.